Leaf surface water, not plant water stress, drives diurnal variation in tropical forest canopy water content. Issue 1 (13th March 2021) - Xu, Xiangtao; Konings, Alexandra G.; Longo, Marcos; Feldman, Andrew; Xu, Liang; Saatchi, Sassan; Wu, Donghai; Wu, Jin; Moorcroft, Paul
Summary: Variation in canopy water content (CWC) that can be detected from microwave remote sensing of vegetation optical depth (VOD) has been proposed as an important measure of vegetation water stress. However, the contribution of leaf surface water (LWs ), arising from dew formation and rainfall interception, to CWC is largely unknown, particularly in tropical forests and other high‐humidity ecosystems. We compared VOD data from the Advanced Microwave Scanning Radiometer for the Earth Observing System (AMSR‐E) and CWC predicted by a plant hydrodynamics model at four tropical sites in Brazil spanning a rainfall gradient. We assessed how LWs influenced the relationship between VOD and CWC. The analysis indicates that while CWC is strongly correlated with VOD ( R 2 = 0.62 across all sites), LWs accounts for 61–76% of the diurnal variation in CWC despite being < 10% of CWC. Ignoring LWs weakens the near‐linear relationship between CWC and VOD and reduces the consistency in diurnal variation. The contribution of LWs to CWC variation, however, decreases at longer, seasonal to inter‐annual, time scales. Our results demonstrate that diurnal patterns of dew formation and rainfall interception can be an important driver of diurnal variation in CWC and VOD over tropical ecosystems and therefore should be accounted for when inferring plant diurnal water stress from VOD measurements. Abstract : See also the Commentary on this article by Gerlein‐Safdi, 231 : 5–7 .